Media Analysis of Biology Teaching Book Grade XII: A Study Based on Science Literation Category - Ivonne Glorifica (Indonesian Journal of Educational Research and Technology, 2021)
The purpose of this study is to analyze Biology textbooks as a source of scientific literacy. To support the research, the authors use descriptive research methods and a cloze test evaluation sheet to evaluate the quality of the books as a source of scientific literacy reading in terms of the scientific literacy category. From the research results, it is found that there are differences in the components of the contents between book A and book B.